Pengaruh Gaya Kepemimpinan, Lingkungan Kerja dan Motivasi Berprestasi terhadap Etos Kerja Pegawai Kementerian Agama Kota Payakumbuh - Rahmad, Rahmad (Jurusan PIPS FKIP UMMY Solok, 2019)
The purpose of this study was to analyze: 1) Effect of leadership style on the work environment, 2) Effect of leadership style on work achievement motivation, 3) Effect of work environment on achievement motivation, 4) Effect of work environment on work ethic, 5) Effect of leadership style on work ethic, 6) Effect of achievement motivation on work ethic. The population of this study were all employees of the Ministry of Religion of the City of Payakumbuh, amounting to 95 people. The number of samples is 49 people. The data analysis technique for testing the hypothesis is path analysis. Research found that: 1) Leadership style has a significant effect on the work environment. 2) Leadership style has a significant effect on achievement motivation. 3) The work environment has a significant effect on employee achievement motivation. 4) Leadership style has a significant effect on work ethic. 5) The work environment has a significant effect on employee work ethics. 6) Motivation for achievement has a significant effect on work ethic. Judging from the direct or indirect influence of the Effect of Leadership Style, Work Environment and Achievement Motivation on the Work Ethic of the Ministry of Religion of Payakumbuh, it is found that the work environment has the greatest influence, namely 26.41%